Home and health among different sub-groups of the ageing population: a comparison of two cohorts living in ordinary housing in Sweden. Issue 1 (December 2016) - Ekström, Henrik; Schmidt, Steven; Iwarsson, Susanne
Abstract Background At present a majority of older people remain in their ordinary homes. Research has generated knowledge about home and health dynamics and increased the awareness of the complexity of housing as related to ageing. As this knowledge is based mainly on research on very old, single-living people in ordinary housing there is a need to study other sub-groups of the ageing population. Thus, the aim of the present descriptive study was to compare a younger old cohort with a very old cohort living in ordinary housing in Sweden in order to shed new light on home and health dynamics in different sub-groups of the ageing population. Methods Cross-sectional study of two population-based cohorts: one aged 67–70 years (n = 371) and one aged 79–89 years (n = 397) drawn from existing Swedish databases. Structured interviews and observations were conducted to collect data about socio-demographics, aspects of home, and symptoms. Besides descriptive statistics we computed tests of differences using the Chi-squared test and Mann–Whitney U-test. Results Accessibility was significantly lower in the very old cohort compared to the younger old cohort even though the former were objectively assessed to have fewer environmental barriers. Those in the very old cohort perceived aspects of their housing situation as worse and were more dependent on external influences managing their housing situation. Although a larger proportion of the very old cohort had more functional limitations 22% were independent in ADL. In the younger old cohort 17% were dependent in ADL. Conclusions Keeping in mind that there were cohort differences beyond that of age, despite fewer environmental barriers in their dwellings the very old community-living cohort lived in housing with more accessibility problems compared to those of the younger old cohort, caused by their higher prevalence of functional limitations. Those in the very old cohort perceived themselves in a less favourable situation, but still as satisfied with housing as those in the younger old cohort. This kind of knowledge is indicative for prevention and intervention in health care and social services as well as for housing provision and societal planning. Further studies based on truly comparable cohorts are warranted.